Mathematical modeling of the additional working body of the excavator - Suleev, Б.Д.; Togizbaeva, Б.Б.; Balabekova, К.Г.; Kenesbek, А. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2021)
The article discusses measures to modernize the working body of the excavator by installing additional working equipment. There has been studied the state of world practices in this area to achieve this goal. There is proposed a new type of working equipment for repairing asphalt concrete pavement based on an excavator instead of standard attachments that provide ease of installation and removal. The working body consisting of an additional milling cutter is designed for cutting asphalt concrete pavement and is made in the form of attachments combined with the main one. There has been developed a mathematical model of a multipurpose hydraulic excavator with an additional milling cutter. The article proposes a simulation model of the milling cutter operation in the Solidworks program. The authors modeled a disk. In Solidworks, there was tested a sample disk using Simulation. The authors conducted detailed studies. The article considers forces acting on the working body. The authors carried out computer studies. As a result, there were obtained loads that showed the effectiveness of the new working body equipped with a cutter. There have been developed mathematical models to calculate the volume of soil cut by the working body, and the milling process is described by the Sant – Venan model. On this basis, there was obtained a rheological model, according to which there was proposed shear deformation. The authors developed a mathematical model of the excavator working body, according to which there was determined the equivalence force. The mathematical model takes into account the spatial nature of deformation and the interaction of transmission elements. The article investigates that the use of such discs makes it possible to clarify the influence of various cutting parameters on the stress state of the cutting disc, to obtain a stress distribution over the width of the cutting disc. The correspondence of the results of the developed and tested mathematical models in the Solidworks computer program allowed us to confirm the performance of the software system, the effectiveness of its application.